2013
DOI: 10.1557/opl.2013.774
|View full text |Cite
|
Sign up to set email alerts
|

Adventures with a Flipped Classroom and a Materials Science and Engineering MOOC : “Fools Go Where Angels Fear to Tread”

Abstract: In the fall of 2012 the Stanford University materials science course Solar Cells, Fuel Cells and Batteries: Materials for the Energy Solution was offered as a flipped class and a massively open online course (MOOC). To the best of our knowledge, this was the first materials science MOOC. Here we describe how the course was implemented, and present results on performance, demographics and other observations that were made. Finally, we provide some perspectives for the future of the implementation of these engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
0
10
1
Order By: Relevance
“…In theory, this allows class-time to be spent answering questions and delving deeper into concepts than would otherwise be possible. A universal conclusion [1][2][3][4][5][6] seems to be that more material can be covered in the flipped format. This does not always appear to lead to improved student learning or mastery of the material, however.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, this allows class-time to be spent answering questions and delving deeper into concepts than would otherwise be possible. A universal conclusion [1][2][3][4][5][6] seems to be that more material can be covered in the flipped format. This does not always appear to lead to improved student learning or mastery of the material, however.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of recent publications have reported efforts in flipping classes ranging freshman-level design courses 1,2 , to sophomore-level mechanics 1 and circuits courses 3 , to a variety of upperlevel engineering courses 1,[4][5][6] . Results of the flipped format implementation have been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the flipped learning format provides various benefits for students and instructors. These benefits can include increased learning gain 3,4 , flexibility [5][6][7][8][9][10][11][12][13][14][15] , increased interaction with peers and the instructor 6,8,9,12,13,[16][17][18][19][20][21][22] , improved professional skills 20,23 , and increased student engagement and preparation 9,13,25,26 . Based, in part, on the potential benefits identified in previous studies, a junior-level transportation engineering course was converted into a flipped format.…”
Section: Introductionmentioning
confidence: 99%
“…They have also explored variations on the flipped model, comparing student outcomes when course requirements, learning tools, and activities are modified 1 . Investigators who have looked at the amount of content coverage in flipped courses [1][2][3][4][5][6] universally conclude that more material can be covered in the flipped format. It is equally clear, however, that increased content coverage does not always lead to better learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature related to flipping classes covers a variety of engineering disciplines and course levels including freshman-level design courses [2][3][4] , sophomore-level mechanics 2 and circuits courses 5 , and a variety of upper-level engineering courses 2,[6][7][8] . Results have shown that the efficacy of the flipped format can vary as much as for any other pedagogy style.…”
Section: Introductionmentioning
confidence: 99%